Bunker consumption of containerships considering sailing speed and wind conditions. (October 2020) - Medina, Josep R.; Molines, Jorge; González-Escrivá, José A.; Aguilar, José
Highlights: Wind is considered to estimate the bunker consumption rate of containerships. Formulas are given to estimate the total resistance force of containerships. Added resistance due to wind and waves increases bunker consumption. Fuel consumption depends on sailing speed, ship route and season. Wind and wave hindcast data can be used to better estimate the bunker consumption. Abstract: This study focuses on container vessel fuel consumption considering the wind conditions along the ship path in the liner route. Simple analytical and semi-empirical formulas are provided to estimate the total resistance force and the bunker consumption rate of fully loaded containerships between 5000 and 15000 TEU considering the effect of wind and the corresponding waves on the Beaufort scale. The bunker consumption rate is proportional to the total resistance force, so bad weather significantly increases fuel consumption. Examples of wind hindcasts and added resistance increases for the Atlantic Ocean, the Mediterranean Sea, and the Indian Ocean are provided for a better "a priori" estimation of the bunker consumption for a containership in a given route and time of the year.